Islamic Civilization and Cultural Dynamics in Southeast Asia: A Comparative Study of Muslim Communities in Indonesia and Thailand - Duski Ibrahim; Hendri Faroza; Agus Srimudin; Dyan Dwianty (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the dynamics of Islamic civilization and cultural expressions in Southeast Asia through a comparative analysis of Muslim communities in Indonesia and Thailand. Southeast Asia represents a unique region where Islam has interacted with diverse local traditions, producing distinctive cultural forms and civilizational patterns. The research aims to explore how Islamic values, cultural traditions, and historical experiences shape the development of Muslim societies in both countries.Using a qualitative comparative approach, this study analyzes historical sources, academic literature, and socio-cultural practices within Muslim communities in Indonesia and Thailand. The research focuses on three main aspects: the historical development of Islam, the interaction between Islamic teachings and local cultures, and the role of cultural practices in shaping contemporary Muslim identity.  The findings reveal that Islamic civilization in Southeast Asia is characterized by adaptability, cultural negotiation, and pluralistic expressions. In Indonesia, Islamic cultural expressions tend to be more institutionalized and integrated within national cultural frameworks, while in Thailand, Muslim communities maintain strong cultural identities through local traditions and religious institutions despite existing within a predominantly Buddhist society.  This study contributes to the broader discourse on Islamic civilization by demonstrating that cultural diversity and local adaptation play significant roles in shaping Muslim societies in Southeast Asia. Understanding these dynamics provides deeper insight into the relationship between religion, culture, and civilization in pluralistic societies.